Involvement of Brn3a-positive spinal dorsal horn neurons in the transmission of visceral pain in inflammatory bowel disease model mice - Nishida, Kazuhiko; Matsumura, Shinji; Kobayashi, Takuya (Frontiers in Pain Research, 2022)
The spinal dorsal horn plays a crucial role in the transmission and processing of somatosensory information. Although spinal neural circuits that process several distinct types of somatic sensations have been studied extensively, those responsible for visceral pain transmission remain poorly understood. In the present study, we analyzed dextran sodium sulfate (DSS)-induced inflammatory bowel disease (IBD) mouse models to characterize the spinal dorsal horn neurons involved in visceral pain transmission. Immunostaining for c-fos, a marker of neuronal activity, demonstrated that numerous c-fos-positive cells were found bilaterally in the lumbosacral spinal dorsal horn, and their distribution was particularly abundant in the shallow dorsal horn. Characterization of these neurons by several molecular markers revealed that the percentage of the Pit1-Oct1-Unc86 domain (POU domain)-containing transcription factor Brn3a-positive neurons among the c-fos-positive neurons in the shallow dorsal horn was 30-40% in DSS-treated mice, which was significantly higher than that in the somatic pain model mice. We further demonstrated by neuronal tracing that, within the shallow dorsal horn, Brn3a-positive neurons were more highly represented in spino-solitary projection neurons than in spino-parabrachial projection neurons. These results raise the possibility that Brn3a-positive spinal dorsal horn neurons make a large contribution to visceral pain transmission, part of which is mediated through the spino-solitary pathway.